Data Leakage of Consumer Personal Data in Telecommunications Services Customer Registration: Who Is Responsible? - Fitri, Winda; Disemadi, Hari Sutra; Rindiyani, Monica (Yustisia Tirtayasa : Jurnal Tugas Akhir, 2024)
The Indonesian government mandates users of SIM cards to register their National Identification Number (NIK) and Family Card number (KK) correctly to activate their prepaid numbers. However, the prepaid card registration policy invites irresponsible individuals who use that personal data without the owner's permission. Therefore, the main issue in this research is, the legal regulations governing the protection of personal data in Indonesia, the role of telecommunications service providers in maintaining the confidentiality of consumer data, and how government agencies play a role in efforts to protect personal data in Indonesia. Type of research used in this research is normative legal research and used data collection technique through literature research. The findings of this study can be summarized as follows, regarding Law No. 27 of 2022 on Personal Data Protection (PDP Law) that provides a strong legal basis for protecting consumer personal data, regulating individual rights to their personal data, and establishing obligations for personal data managers. As well as telecommunications service providers have the responsibility to provide clear and transparent information to consumers about how their personal data will be used and processed. Along with the government agencies function to enact and supervise personal data protection regulations and educate public about data privacy awareness.